2019
DOI: 10.34297/ajbsr.2019.06.001010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fertilizer Subsidy Programme on Maize Income in the Northern Region of Ghana

Abstract: This study principally assessed the impact of fertilizer subsidy programme on maize income in the Northern Region. Sample sizes of 400 respondents were interviewed using questionnaires. Secondary data was also collected for the study and the results analyzed. Simple random sampling techniques was used in selecting respondents. The data was analyzed using appropriate descriptive statistics and Propensity Score Matching (PSM). The study revealed that majority of smallholder participated in the fertilizer subsidy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Another study conducted by Allotey et al (2019) examined the effects of a fertilizer subsidy program on maize income in Northern Ghana. Utilizing the propensity score matching (PSM) method to analyze data from 400 respondents collected in 2019, the findings indicated that the majority of maize farmers joined the program due to the high poverty levels in the area.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted by Allotey et al (2019) examined the effects of a fertilizer subsidy program on maize income in Northern Ghana. Utilizing the propensity score matching (PSM) method to analyze data from 400 respondents collected in 2019, the findings indicated that the majority of maize farmers joined the program due to the high poverty levels in the area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although several studies in Vietnam and other countries have investigated the effect of participation in rural and agricultural support programs on household income, the results of these papers have not reached a consensus. The research of Sikwela and Mushunje (2013), Tran et al (2023), Barslund and Tarp (2008), Wordofa and Sassi (2018), Bhuiya et al (2016), and Allotey et al (2019) provided evidence on the positive impact of participating in government's aid programs on the income of households, especially those in rural areas. In addition to improving household income and reducing poverty, these programs also help increase property values, education spending, and food spending for participants.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Andani et al (2020) employed endogenous switching regression to simultaneously evaluate the determinants of participation in fertilizer subsidy and its impact on maize productivity. Allotey et al (2019) examined the impacts of fertilizer subsidy on maize income in Northern Ghana using PSM. Imoru and Ayamga (2015) employed Tobit regression to assess farmers' participation in fertilizer subsidy and its effects on fertilizer use in Northern Region of Ghana.…”
Section: Ijppm 731mentioning
confidence: 99%
“…(2020) employed endogenous switching regression to simultaneously evaluate the determinants of participation in fertilizer subsidy and its impact on maize productivity. Allotey et al. (2019) examined the impacts of fertilizer subsidy on maize income in Northern Ghana using PSM.…”
Section: Introductionmentioning
confidence: 99%
“…A propensity score matching method (PSM) was employed by Allotey (2019) to evaluate the effect of the fertiliser subsidy programme on the income of the household. The study found that the fertiliser subsidy programme has a direct contribution to household income.…”
Section: Empirical Reviewmentioning
confidence: 99%